2007
DOI: 10.1183/09031936.00073005
|View full text |Cite
|
Sign up to set email alerts
|

Increased galectin-3 expression and intra-epithelial neutrophils in small airways in severe COPD

Abstract: Galectins-1 and -3 regulate epithelial proliferation/apoptosis and neutrophil activation, and are implicated in lung cancer and asthma. The role of galectins in chronic obstructive pulmonary disease (COPD), characterised by epithelial changes and neutrophil infiltration, remains unknown.In the present study, galectin-1 and -3 expression was assessed by immunohistology in the bronchial epithelium of lung specimens from eight severe COPD patients and compared with nine nonsmokers and six smokers without COPD. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 61 publications
(95 reference statements)
1
55
1
2
Order By: Relevance
“…In our study we used ASM cells from smokers with and without COPD. The induction of CXCL8 and CXCL1 by CSE in ASM cells from both groups may reflect the observation that neutrophils are increased in COPD patients [31] and smokers without COPD [32]. Furthermore, as low concentrations of CSE induced CXCL1 in the COPD cells only, this suggested that these cells were hyperresponsive to CSE, and may explain why some smokers develop COPD and others do not.…”
Section: Discussionmentioning
confidence: 89%
“…In our study we used ASM cells from smokers with and without COPD. The induction of CXCL8 and CXCL1 by CSE in ASM cells from both groups may reflect the observation that neutrophils are increased in COPD patients [31] and smokers without COPD [32]. Furthermore, as low concentrations of CSE induced CXCL1 in the COPD cells only, this suggested that these cells were hyperresponsive to CSE, and may explain why some smokers develop COPD and others do not.…”
Section: Discussionmentioning
confidence: 89%
“…Significant changes in oxidant responsive genes have been observed in the epithelium of healthy smokers as well as COPD patients [94]. A small increase in the proliferative rate of the epithelium of small airways of COPD patients has been reported [95], together with increased expression of galectin-1 in the epithelium, which could be involved in epithelial proliferation and apoptosis.…”
Section: Epithelial Changesmentioning
confidence: 87%
“…The results demonstrated that SAEC were more responsive to acute CSE exposure than NHBE cells, with regard to VEGF reduction. Although some reports have proposed certain differences of cellular population or gene expression, such as galectin-3 and Ki-67, in small and large AEC in COPD [43], no previous studies have addressed the molecular mechanisms responsible for the different responses to CS exposure between these two types of AEC. Further studies are needed to demonstrate the molecular basis upon which SAEC are more responsive to CSE exposure than NHBE cells with regard to VEGF reduction.…”
Section: Discussionmentioning
confidence: 99%